Kim - Kipling, Rudyard, 1865-1936. (Warszawa : Ludowa Spoldzielnia Wydawnicza, 1987)
Polish translation of Kipling's "Kim" a tale of India and the English rule by the Nobel Prize winner.
Translation of: Kim.
Keywords: Irish -- India -- Fiction; Orphans -- Fiction; Lamas -- Fiction; Boys -- Fiction; India -- Fiction